Evaluasi Pelaporan Tanggung Jawab Sosial pada PT Bukit Asam (Persero) Tbk - Ria Panggabean, Rosinta (Binus Business Review, 2013)
This study uses a content analysis framework that provides information on the comprehensiveness of corporate social responsibility (CSR) reporting, an important aspect of social and environmental accountability. Comprehensive reporting requires three types of information for each disclosed CSR item: (i) vision and goals, (ii) management approach, and (iii) performance indicators. This study evaluates the comprehensiveness of CSRreporting using the 2011 annual report of PT Bukit Asam (Persero) Tbk. The content analysis reveals a low level of comprehensive reporting. This finding complements those of prior studies on the completeness of CSR reporting.